Effects of water discharge on fledging time, growth, and survival of piping plovers on the Missouri River1. Issue 3 (28th January 2013) - Catlin, Daniel H.; Felio, Joy H.; Fraser, James D.
Abstract: River flow management and modification is a global issue, and its effects on river‐dependent organisms are pervasive. Flow modification can directly affect avian species through mortality or habitat loss, but less is known about indirect and sublethal effects of flow modification on reproductive output in these species. Young birds are more vulnerable to predation between hatching and fledging than after flight is achieved, but tradeoffs must be made to balance growth and survival. Predation pressure appears to be a significant factor affecting the time to fledging in altricial birds, but less is known about this threat for precocial birds. Birds reaching fledging earlier should have greater rates of survival to migration because their predator escape repertoire includes flight at an earlier age. We evaluated the effect of varying outflows from the Gavins Point Dam on the growth, age at fledging, and survival of piping plover ( Charadrius melodus ) chicks on the Missouri River (2006–2009). The study was characterized by 2 relatively high flow years (2006 and 2009) and 2 relatively low flow years (2007 and 2008). We used success rate in recapturing chicks in capture–mark–recapture models as an index for fledging. We attempted to recapture all chicks ( n  = 1, 099) by hand every 3–4 days throughout the season to acquire morphological measurements. Models indicated that as flows from the dam increased, age at fledging increased. We also found that increasing flows were associated with decreasing daily survival rates ( β flow  = −2.401, 95% CI: −4.351 to −0.452). Flow was also negatively related to chick mass gain, but we found less evidence for an effect on wing‐chord length. Increased flows covered wet‐substrate foraging habitat, and likely affected plover reproductive output directly through chick survival and indirectly through decreased growth and increased fledging times. © The Wildlife Society, 2013